CEO should be a generalist or specialist? Empirical foundations for leadership research - Soomro, Mansoor Ahmed; Hanafiah, Mohd Hizam (Ifma Publishing, 2022)
Chief Executive Officer is the senior most leader in charge of managing an organization. This paper reviews peer-reviewed empirical studies on Chief Executive Officers, and extends the empirical arguments to Generalist and Specialist Chief Executive Officers explicitly, and in the process conceptualizes three schools of thought: Technical, Managerial and Intrapreneurial. These empirical arguments have been contrasted with dependent, independent, moderating and mediating variables from the leadership literature. Additionally, the empirical studies have been matched with two broad and three narrow leadership domains, to provide insight for further research in the area of corporate leadership. This paper indicates that Generalist Chief Executive Officers and Specialist Chief Executive Officers have different standpoints for different reasons.